BrazIliaN Type 1 & 2 DiabetEs Disease Registry (BINDER): longitudinal, real-world study of diabetes mellitus control in Brazil - de Almeida-Pititto, Bianca; Eliaschewitz, Freddy G.; de Paula, Mauricio A.; Ferreira, Graziela C. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Introduction This study aimed at assessing the patterns of care and glycemic control of patients with diabetes (DM) in real life during a follow-up of 2 years in the public and private health sectors in Brazil. Methods BINDER was an observational study of patients >18 years old, with type-1 (T1DM) and type-2 DM (T2DM), followed at 250 sites from 40 cities across the five regions of Brazil. The results for the 1,266 participants who were followed for 2 years are presented. Main results Most patients were Caucasians (75%), male (56.7%) and from the private health sector (71%). Of the 1,266 patients who entered the analysis, 104 (8.2%) had T1DM and 1162 (91.8%) had T2DM. Patients followed in the private sector represented 48% of the patients with T1DM and 73% of those with T2DM. For T1DM, in addition to insulins (NPH in 24%, regular in 11%, long-acting analogues in 58%, fast-acting analogues in 53%, and others in 12%), the patients received biguanide (20%), SGLT2-I (4%), and GLP-1Ra (<1%). After 2 years, 13% of T1DM patients were using biguanide, 9% SGLT2-I, 1% GLP-1Ra, and 1% pioglitazone; the use of NPH and regular insulins decreased to 13% and 8%, respectively, while 72% were receiving long-acting insulin analogues, and 78% fast-acting insulin analogues. Treatment for T2DM consisted of biguanide (77%), sulfonylureas (33%), DPP4 inhibitors (24%), SGLT2-I (13%), GLP-1Ra (2.5%), and insulin (27%), with percentages not changing during follow-up. Regarding glucose control, mean HbA1c at baseline and after 2 years of follow-up was 8.2 (1.6)% and 7.5 (1.6)% for T1DM, and 8.4 (1.9)% and 7.2 (1.3)% for T2DM, respectively. After 2 years, HbA1c<7% was reached in 25% of T1DM and 55% of T2DM patients from private institutions and in 20.5% of T1DM and 47% of T2DM from public institutions. Conclusion Most patients did not reach the HbA1c target in private or public health systems. At the 2-year follow-up, there were no significant improvements in HbA1c in either T1DM or T2DM, which suggests an important clinical inertia.